Slice profile and B1 corrections in 2D magnetic resonance fingerprinting - Ma, Dan; Coppo, Simone; Chen, Yong; McGivney, Debra F.; Jiang, Yun; Pahwa, Shivani; Gulani, Vikas; Griswold, Mark A. (Magnetic resonance in medicine, 2017)
Purpose The goal of this study is to characterize and improve the accuracy of 2D magnetic resonance fingerprinting (MRF) scans in the presence of slice profile (SP) and B1 imperfections, which are two main factors that affect quantitative results in MRF. Methods The SP and B1 imperfections are characterized and corrected separately. The SP effect is corrected by simulating the radiofrequency pulse in the dictionary, and the B1 is corrected by acquiring a B1 map using the Bloch‐Siegert method before each scan. The accuracy, precision, and repeatability of the proposed method are evaluated in phantom studies. The effects of both SP and B1 imperfections are also illustrated and corrected in the in vivo studies. Results The SP and B1 corrections improve the accuracy of the T1 and T2 values, independent of the shape of the radiofrequency pulse. The T1 and T2 values obtained from different excitation patterns become more consistent after corrections, which leads to an improvement of the robustness of the MRF design. Conclusion This study demonstrates that MRF is sensitive to both SP and B1 effects, and that corrections can be made to improve the accuracy of MRF with only a 2‐s increase in acquisition time. Magn Reson Med 78:1781–1789, 2017. © 2017 International Society for Magnetic Resonance in Medicine.